Desenvolvimento de um pluviômetro automático de baixo custo utilizando material reutilizável para internet das coisas - Silva, Nadison Francisco da (Universidade Federal Rural do Semi-Árido, 2018)
This work aims to develop and validate a low cost automatic rain gauge, using recyclable material, containing WiFi module and magnetic sensor, aimed at applications in intelligent agriculture based on internet of things. With this, it is hoped to contribute to the increase of the agricultural productivity and the economy of the water and energy resources, with a plantation of sustainable form, for small and medium farmers, allowing the monitoring of the volume of rain, temperature and humidity, the processing of this data, from anywhere in the world, at any time and using any device that connects to the internet. Thus, with this information, one can help in deciding which farming crop, when to fertilize the land, plant, irrigate, apply defenses and harvest, contributing to increased production and minimizing losses. This rain gauge was calibrated and field tested for 100 days, in a comparative manner, where its accuracy and applicability were proven, as well as its low cost and sustainable appeal with the use of recyclable material.
Monografia
Keywords: Internet das coisas; Pluviômetro automático; Material reciclável; Agricultura inteligente; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA